MENCAPAI KEUNGGULAN KOMPETITIF MELALUI PENGEMBANGAN SUMBER DAYA MANUSIA - Larasati, Sri (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2011)
The Changes of business environment really influence the organization (company) and it will bring the effects to the company, like production additional value, control, management, teamwork, job arrangement, activity process, communication and delegation. To fase the changes, we need to think about the management of human resource in various types off organization in the future.This will encourage us to find the solution in order to face the changes of business of environment. The development of human resource in the business organization is absolutely need in facing the future challenge,by fixing the effectiveness and productivity of human resource to have thestrength Of competitive. Repositioning the vision, mission,and corporate values,which is followed by company strategy,espe Cially in the human reource management,can start the response of company to the changes. The development strategy of human resource has to be flexible in accepting the new ideas by doing the reformation fundamentally to the practices and conventional policies, therefore,it can guarantee the successful in achieving the goals of competitive superiority. Keyworks; superiority competitive, development, human resource.